2023
DOI: 10.1088/1742-6596/2466/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and IoT-based smart farming for enhancing the crop yield

Abstract: The lack of favourable atmospheric conditions leads to the loss of many crops each year. In India alone, over 11 billion dollars are lost. By combining IoT and machine learning technologies, this team has created a system that integrates agriculture’s three primary operations: crop selection, autonomous watering, and fertiliser suggestion. The following crops—Apple, Rice, Maize, Grape, Banana, Orange, Cotton, and Coffee—were considered in the study. Three systems are covered in the paper: The crop recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…ACRIS module is another crop recommender system implemented [23]. Sundaresan et al [24] considered some crops like bananas, oranges, cotton, coffee, and many more for the recommendation system. Thangavel et al [25] identified agriculture machinery usage by districts around South Tamil Nadu to predict suitable machinery for that area.…”
Section: Introductionmentioning
confidence: 99%
“…ACRIS module is another crop recommender system implemented [23]. Sundaresan et al [24] considered some crops like bananas, oranges, cotton, coffee, and many more for the recommendation system. Thangavel et al [25] identified agriculture machinery usage by districts around South Tamil Nadu to predict suitable machinery for that area.…”
Section: Introductionmentioning
confidence: 99%